2011
DOI: 10.1145/1970378.1970380
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a command recommendation system for software applications

Abstract: We examine the use of modern recommender system technology to aid command awareness in complex software applications. We first describe our adaptation of traditional recommender system algorithms to meet the unique requirements presented by the domain of software commands. A user study showed that our item-based collaborative filtering algorithm generates 2.1 times as many good suggestions as existing techniques. Motivated by these positive results, we propose a design space framework and its associated algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 66 publications
1
54
0
Order By: Relevance
“…This metric considers the frequency of actual usage. Command frequency has been used previously to profile user expertise (Li, Matejka, Grossman, Konstan, & Fitzmaurice, 2011;Matejka, Li, Grossman, & Fitzmaurice, 2009;Rooke, Grossman, & Fitzmaurice, 2011). For UI Expertise, a higher frequency of usage with modifier hotkeys may be a sign of a higher level of expertise (Grossman, Dragicevic, & Balakrishnan, 2007).…”
Section: Measurement Typementioning
confidence: 99%
See 2 more Smart Citations
“…This metric considers the frequency of actual usage. Command frequency has been used previously to profile user expertise (Li, Matejka, Grossman, Konstan, & Fitzmaurice, 2011;Matejka, Li, Grossman, & Fitzmaurice, 2009;Rooke, Grossman, & Fitzmaurice, 2011). For UI Expertise, a higher frequency of usage with modifier hotkeys may be a sign of a higher level of expertise (Grossman, Dragicevic, & Balakrishnan, 2007).…”
Section: Measurement Typementioning
confidence: 99%
“…Research on complex applications has shown that any individual user may only use a subset of a software application's commands (McGrenere & Moore, 2000), and some commands have higher relevance to users than others (Li et al, 2011;Matejka et al, 2009). We define component relevance as the level of importance that a component of a software application has to a user, based to that user's day-to-day tasks.…”
Section: Component Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Determining the right length of this training period is difficult -we wanted the recommendations to start as soon as possible, but only after we reliably know what commands the user is already aware of. To minimize the time needed for training, we ran a pilot test by analyzing data from 27 users (Li et al 2011). On a daily interval, we measured the rate at which new commands were used (had not been previously observed for that user), across a period of 4 weeks ( figure 9).…”
Section: Training Before Recommendingmentioning
confidence: 99%
“…This project continued to evolve and we explored the design space of a contextual software command recommender system and completed a six-week user study (Li et al 2011 Product Year assume such assistance would be readily available.…”
mentioning
confidence: 99%